Perancangan Sistem Manajemen Kegiatan Magang Mahasiswa Berbasis Web: Studi Kasus: SMK Parulian 2 Medan - Akmal Nasution; Niko Surya Atmaja; Arpan Arpan (Lembaga Pengembangan Kinerja Dosen, 2026)
SMK Parulian 2 Medan is one of the educational institutions that accepts student interns from various universities. The management of internship activities involves various processes, including student registration, placement, activity recording, monitoring, and internship report management. Based on observations and interviews conducted at SMK Parulian 2 Medan, internship management is still carried out using documents and simple file storage, causing difficulties in data retrieval, information management, and activity monitoring. This study aims to design a web-based internship activity management information system to support the management of internship data in an integrated manner. The proposed program provides features for managing student data, internship placements, activity records, monitoring processes, and internship reports. The implementation of the program is expected to improve the effectiveness of internship data management, accelerate information retrieval, facilitate monitoring activities, and support reporting processes. Therefore, the program can assist SMK Parulian 2 Medan in improving the quality and efficiency of student internship management